Antioxidant action of six Trifolium species in blood platelet experimental system in vitro - Kolodziejczyk-Czepas, J. (Mol Cell Biochem, 2015)
This study includes a comparative evaluation of antioxidant effects of plant extracts (1.5–50.0 μg/ml), derived from six clover (Trifolium) species: T. alexandrinum L., T. fragiferum L., T. hybridum L., T. incarnatum L., T. resupinatum var. majus Boiss., and T. resupinatum var. resupinatum L. Chemical profiles of the extracts contained three or four groups of (poly)phenolic compounds such as phenolic acids, clovamides, isoflavones, and other flavonoids. Antioxidant properties of Trifolium extracts were assessed as the efficacy to reduce oxidative and nitrative damage to blood platelets, exposed to 100 μM peroxynitrite-induced oxidative stress in vitro. Antioxidant actions of the examined extracts were determined by the following biomarkers of oxidative stress: thiol groups, 3-nitrotyrosine, lipid hydroperoxides, and thiobarbituric acid-reactive substances (TBARS). Despite the significant differences in the chemical composition (the total phenolic concentrations varied between 11.30 and 52.55 mg/g of dry mass) of Trifolium extracts, we observed noticeable protective effects of almost all tested plant preparations. The T. alexandrinum extract, containing the highest concentration of phenols, was the most effective antioxidant among the tested extracts. On the other hand, the T. incarnatum extract, which contained a comparable total phenolic content (49.77 mg/g), was less efficient in prevention of tyrosine nitration and generation of TBARS. These findings indicate on the important role of individual phenolic components of the examined clover extracts for the final antioxidative effects. Antioxidative properties of the remaining extracts were noticeably weaker.